GWAS identifies a polyembryony locus in mango: development of KASP and PACE markers for marker-assisted breeding - Ali, Gul Shad; Eltaher, Shamseldeen; Li, Jin; Freeman, Barbie; Singh, Sukhwinder (Frontiers in Plant Science, 2025)
Apomixis is a horticultural trait that enables clonal propagation of hybrids by producing asexual embryos from maternal cells in the ovule without meiosis. Many mango cultivars exhibit apomictic polyembryony, where one embryo develops from zygotic tissues and the rest from nucellar tissues, resulting in seedlings that are genetically identical to the mother tree. In Mangifera indica L. commercially important rootstocks are raised from apomictic seeds, which are then grafted with desired cultivars. Identifying molecular markers for polyembryony and understanding its genetics would facilitate introducing this trait in commercially important cultivars. In this report, genome-wide association studies were conducted on a diversity panel consisting of 42 polyembryonic and 42 monoembryonic M. indica cultivars using high-density single nucleotide polymorphism (SNP) markers. These studies revealed that the polyembryony locus is in a 360-kb region on linkage group 17 of the ‘Alphonso’ reference genome. This locus contains the MiRWP/MiRKD4 gene, which codes for an RWP–RK domain-containing protein previously implicated in citrus apomixis. Comparative genomic analyses revealed synteny between the citrus and the mango polyembryony loci, suggesting a common evolutionary mechanism for this trait. A total of 29 SNP markers in this locus were significantly associated with polyembryony in M. indica. Five of these markers were developed into convenient genotyping assays using competitive allele-specific PCR chemistry implemented in two different genotyping platforms – Kompetitive Allele-Specific PCR (KASP) and PCR allele competitive extension (PACE). The utility of these assays was validated and demonstrated in diverse germplasm collection and open-pollinated mango breeding populations with known pedigrees and polyembryony phenotypes. These SNP markers, especially those flanking the MiRWP/MiRKD4 gene, provide a valuable tool for mango breeders to select polyembryonic progenies at the seedling stages in mango breeding programs.